A new diagnostic method for evaluation of cardiosurgery wound healing. Issue 1 (2nd January 2016) - Nowakowski, Antoni; Siondalski, Piotr; Moderhak, Mateusz; Kaczmarek, Mariusz
Abstract : One of important and still unsolved problems in medicine is the question of objective and quantitative evaluation of post-surgery wound healing. The aim of this research is to analyse possibility and value of using the newly elaborated infrared imaging procedure – Active Dynamic Thermography (ADT) – for quantitative description of wound healing processes in cardiosurgery. Both, classical thermal figures of merit as well as ADT descriptors are compared from the point of view of objective, quantitative estimation of wound state. Temporal properties of thermal transients are proposed for objective quantitative description of a tested wound and for classification of healing processes as normal or suspected, requesting a special care. Algorithms enabling evaluation of surgical wound healing process are discussed in terms of possible implementation of the method into clinical practice for proper classification of patients for discharging from a hospital and further treatment at home or for prolonged treatment at the hospital.